Preliminary remarks on the production and distribution of terra sigillata excisa in Northern Italy: New data from recent excavations at Calvatone-Bedriacum - Palmieri, Lilia (Rei Cretariae Romanae Fautorum Acta, 2017)
The vicus of Bedriacum, a small Roman site in Northern Italy identified two kilometres away from the modern town of Calvatone (about 35 km east of Cremona), has been under investigation since 1986 by the University of Milan, in collaboration with the Superintendency for the Archaeological Heritage of Lombardy, expanding the research carried out by the Superintendency in 1957–1961. The synergy between the two institutions has allowed the systematic exploration of that part of the Roman vicus which is located within the limits of the so called “area di proprietà provinciale”, a rural area purchased in 1964 by the Province of Cremona after the notification by the Superintendency of its archaeological interest.